(untitled) (Scientific journal of the Fergana State University, 2025)
Through the humanities, young people learn to understand and respect various cultures and values, participate effectively in intercultural communication, and appreciate universal values. This research presents methodological foundations that contribute to the spiritual development of youth and their formation as responsible citizens in the global community by harmonizing national and global values.